Essentials of understanding psychology - Feldman, Robert S. (Boston, MA : McGraw-Hill, 2011)
Your students are individuals. Do your teaching materials treat them that way? This title presents an adaptive diagnostic tool that generates a personalized study plan to help students 'know what they know' while guiding them to understand and learn what they don't know through engaging interactivities, exercises, and readings
Includes glossary, bibliographical references and index
Keywords: Psychology -- Textbooks